Immobilizing hydrolytic active Papain on biodegradable PLLA for biofilm inhibition in cardiovascular applications - Teske Michael (De Gruyter, 2020)
The use of biomaterials in medicine is becoming increasingly important. One of the main concerns is the foreign body associated infection caused by direct microbial contamination or clinical infections. The bacterial biofilm formation on biomaterials depends on their surface properties. Therefore, several anti-adhesive surface modifications were developed. Nevertheless, the demand for antimicrobial agents that prevent bacterial colonisation is still largely unmet. The immobilization of active antimicrobial agents, such as antibacterial peptides or enzymes, offers a potential approach to achieve long-lasting effectiveness. In this investigation, the hydrolytic enzyme papain with its published antibacterial activity was covalently immobilized on the well-established biodegradable biomaterial poly-L-lactic acid (PLLA). For the characterization of the enzymes on the PLLA surfaces, the protein content and enzyme activity were determined. A biofilm assay was performed to test the effect of the papain-modified PLLA samples on the biofilm-forming bacterial strain Clostridioides difficile, one of the most frequently occurring human nosocomial pathogens. The investigated hydrolytic enzyme papain could be immobilized by coupling via the crosslinker EDC to the PLLA surface. Detection was performed by determination of the amount of protein and the reduced biofilm growth after 24 h and 72 h compared to the reference.